Preparation method and application of electric anode film for efficiently breaking metal organic complex
By growing a modified titanium dioxide nanoarray tube on a porous titanium substrate and loading lead dioxide and iron oxide, an electroanode film was prepared, which solved the problem that metal organic complexes in electroplating wastewater were difficult to break and degrade, and achieved efficient pollutant degradation effect.
Patent Information
- Application Number
- CN202411642512.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to efficiently break and degrade metal organic complexes, especially Ni-EDTA, in electroplating wastewater, which are difficult to discharge pollutants according to standards and cause environmental hazards.
A modified titanium dioxide nanoarray tube is grown on a porous titanium substrate and loaded with lead dioxide and iron oxide thereon to form a composite electrocatalyst for the preparation of the electroanode film. The electroanode film is prepared by electrochemical deposition technology and can efficiently break and degrade metal organic complexes in a flow-through reactor.
It significantly improves the specific surface area and electrocatalytic active sites of the electrode, enhances the degradation efficiency of metal-organic complexes, and can efficiently break and degrade pollutants such as Ni-EDTA, solving the problem that traditional technology is difficult to meet emission standards.
Smart Images

Figure CN119503966A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic oxidation and water treatment, and in particular to a method for preparing an electro-anodic membrane for efficiently breaking metal organic complexes and its application. Background Art
[0002] Nonferrous metals are one of the basic raw materials of modern industry. With the acceleration of industrialization, the demand for nonferrous metals is increasing. Among them, nickel has a silvery metallic luster, good ductility and ferromagnetism, can be highly polished and is corrosion-resistant. It is one of the most widely used nonferrous metals, especially in electroplating, electronics, construction and other industries. It plays an indispensable role. Due to the large-scale use of nickel, it is inevitable that excessive discharge of metallic nickel in the environment occurs. When high-concentration metal wastewater enters the environment, it is not easy to fix in the soil, but accumulates in animals and plants along the food chain cycle, eventually causing serious harm to the biological community and human body.
[0003] The electroplating industry is the main source of nickel pollution. In the nickel plating process, in order to control the metal deposition rate, improve the stability of nickel plating, and improve the quality of the coating, a large amount of brighteners, chelating agents, surfactants, etc. are added to the nickel plating solution, making the composition of electroplating wastewater more complex. In particular, strong chelating agents, represented by ethylenediaminetetraacetic acid (EDTA), will form a very stable complex (Ni-EDTA) with metallic nickel, making it difficult for metallic nickel to be directly affected by the outer layer of substances, and even more difficult to actively break the complex and release it, which seriously affects the removal efficiency of metallic nickel, making it difficult for nickel plating wastewater to meet the discharge standards, causing long-term potential harm to the environment.
[0004] Since metal complexes are difficult to break and separate, conventional treatment methods such as adsorption, chemical precipitation, and ion exchange are difficult to effectively remove them, so some expensive advanced oxidation methods (AOPs) are widely used. After AOPs treatment, organic matter is mineralized, metallic nickel is dissociated, and then effectively removed by chemical precipitation, adsorption, flocculation, and other methods. Common AOPs include Fenton and Fenton-like methods, ozone oxidation, and discharge plasma oxidation. However, Fenton and Fenton-like methods are limited by the addition of a large amount of oxidizing agents, the limited solubility of ozone in ozone oxidation, and the complex operation and high energy consumption of discharge plasma oxidation, which greatly increase the treatment cost and cannot be applied on a large scale.
[0005] Electrochemical advanced oxidation process (EAOP) can use electrons to replace oxidizing or reducing agents, avoiding the addition of reagents. It also has mild reaction conditions, simple equipment, and high energy efficiency. It makes up for the shortcomings of other technologies to a large extent and is currently an effective treatment technology for metal complex wastewater.
[0006] In EAOP, the selection of electrode materials is particularly important. Compared with traditional materials, one-dimensional nanomaterials have significant advantages in structure and performance. Structurally, one-dimensional nanomaterials usually have nanoscale size and length, with a unique aspect ratio, which can provide a larger specific surface area and directional electron ion conduction direction; in terms of performance, they show strong stress tolerance and short axial electron ion transmission path. Therefore, electrocatalysts based on one-dimensional nanomaterials have become a research hotspot. However, many nanomaterials need to be connected to the current collector through a binder, which not only poses the risk of loose connection, but also inevitably increases the internal resistance of the electrode and may cover up the active sites. The method of directly growing nanostructured self-supporting materials on a conductive substrate does not require a binder, can provide a direct and fast channel for electron transmission, and its solid structure can improve the stability of the electrode.
[0007] Titanium substrates are widely used due to their light weight, high strength, excellent corrosion resistance, good electrical conductivity and electrocatalytic properties, long life, and stable size. Therefore, self-supporting electrodes with titanium as a conductive substrate and titanium dioxide nanotube arrays vertically oriented and grown on a titanium substrate as a template can effectively improve electrode performance.
[0008] However, the conventional titanium dioxide nanotube array has the inherent defect of poor conductivity, so it can be self-doped with Ti by reduction method. 3+ To improve the performance of titanium dioxide nanotube arrays, Ti 3+ Doping can significantly improve the performance of TiO by enhancing electronic conductivity, increasing electron concentration, improving chemical bonds and other multiple mechanisms. 2 conductivity.
[0009] Furthermore, by loading lead dioxide on the titanium dioxide nanotube array, the oxygen evolution reaction (OER) potential can be effectively improved, and physically adsorbed OH can be efficiently produced, which can completely mineralize the pollutants; at the same time, the introduction of iron oxide as an active dopant can effectively improve the Pb 2+ The risk of leaching and changes the solid-state properties of the electrode, resulting in a larger specific surface area and additional electrocatalytic active sites.
[0010] The anode membrane prepared after a series of modifications is used in a flow-through reactor, which overcomes the mass transfer problem of the traditional system, increases the contact oxidation time between the electrode and the active substance and the pollutants, and thereby improves the degradation efficiency of metal organic complexes, and can effectively solve the problem of metal organic complex pollution in electroplating wastewater. Summary of the invention
[0011] In view of this, the object of the present invention is to provide a method for preparing an electro-anodic membrane capable of efficiently breaking and degrading metal organic complexes and its application.
[0012] In order to achieve the above object, the present invention provides the following technical solutions:
[0013] The present invention provides an electric anode film, comprising a substrate film and a composite electrocatalyst stacked in sequence, wherein the composite electrocatalyst comprises a modified titanium dioxide nanotube array and a lead dioxide-doped iron oxide catalyst layer; the modified titanium dioxide nanotube array comprises native NTAs, Ti / TiO 2 NTAs, r-Ti / TiO 2 NTAs.
[0014] Preferably, the titanium dioxide nanotube array has an inner diameter of 20 to 120 nm, an outer diameter of 50 to 200 nm, and a length of 2.0 to 4.0 μm.
[0015] The present invention also provides a method for preparing the electric anode film described in the above technical solution, comprising the following steps:
[0016] The porous titanium substrate is placed in an acid solution for acidification pretreatment, and after standing for a period of time, a pretreated substrate is obtained;
[0017] The pretreated porous titanium substrate is sequentially subjected to first anodization, ultrasonic stripping, second anodization, and ultrasonic cleaning to obtain native NTAs;
[0018] The native NTAs were calcined to obtain anatase-type titanium dioxide nanotube array supported on a titanium substrate, denoted as Ti / TiO 2 NTAs;
[0019] The Ti / TiO 2 NTAs are placed in a reducing solution for cathode reduction to obtain Ti 3+ Doped titanium dioxide nanotube array, denoted as r-Ti / TiO 2 NTAs;
[0020] The r-Ti / TiO 2 NTAs are placed in a deposition solution and electrochemically deposited using a DC power supply box to obtain the electrochemical anode film (Ti / TiO 2 NTAs / PbO 2 -Fe).
[0021] Preferably, the acid solution comprises hydrofluoric acid, nitric acid and water in a volume ratio of 1:(2-5):(5-30); the temperature for the acidification pretreatment is 20-40° C., and the pretreatment time is 10-60 s.
[0022] Preferably, the first anodizing solution comprises ammonium fluoride, water, and ethylene glycol in a mass ratio of 1:(3-6):(200-300); the anodizing cathode comprises a graphite plate, a titanium sheet, or a platinum sheet, and the distance between the anode and cathode is 1-4 cm; the anodizing temperature is 20-40°C, the oxidation time is 0.5-10h, and the oxidation voltage is 20-120V.
[0023] Preferably, the ultrasonic peeling solution comprises deionized water or anhydrous ethanol; the ultrasonic peeling power is 80 to 200 W; and the ultrasonic peeling time is 5 to 30 min.
[0024] Preferably, the solution composition of the second anodizing comprises ammonium fluoride, water, and ethylene glycol, and the volume ratio thereof is 1:(2-5):(300-500); the cathode of the anodizing comprises a graphite plate, a titanium sheet or a platinum sheet, and the distance between the anode and cathode is 1-4 cm; the anodizing temperature is 20-40°C, the oxidation time is 0.5-10h, and the oxidation voltage is 20-120V.
[0025] Preferably, the ultrasonic cleaning solution comprises deionized water or anhydrous ethanol; the ultrasonic cleaning power is 80 to 200 W; and the ultrasonic cleaning time is 5 to 30 min.
[0026] Preferably, the calcination temperature is 200-500° C., the heating rate to the calcination temperature is <10° C. / min, and the holding time is 0.5-8 h.
[0027] Preferably, the solution composition of the cathode reduction includes sulfuric acid and water, and the volume ratio thereof is 1:10-200; the anode of the cathode reduction includes a graphite plate, a titanium sheet or a platinum sheet, and the distance between the cathode and the cathode is 1-4 cm; the cathode reduction temperature is 20-60°C, the reduction time is 5-30 min, and the reduction current density is 1-20 mA / cm 2 .
[0028] Preferably, the deposition solution comprises an acid solution, a soluble lead source, a soluble iron source, and a soluble fluorine source; the molar concentration of the deposition solution is 0.01 to 1 mol / L; the type of the acid solution comprises nitric acid, hydrochloric acid or sulfuric acid; the molar concentration of the acid solution is 0.01 to 1 mol / L; the soluble lead source in the deposition solution comprises lead nitrate, lead chloride or lead sulfate, and the concentration of the soluble lead source is 0.01 to 1 mol / L; the soluble iron source in the deposition solution comprises ferric nitrate, ferric chloride or ferric sulfate, and the concentration of the soluble iron source is 0.01 to 1 mol / L; the concentration of the soluble fluorine source in the deposition solution is 0.1 to 10 mol / L; the cathode of the deposition reaction comprises a graphite plate, a titanium sheet or a platinum sheet, and the distance between the anode and cathode is 1 to 4 cm; the temperature of the deposition reaction is 30 to 60°C, the deposition time is 10 to 60 min, and the deposition current density is 10 to 50 mA / cm 2 .
[0029] The present invention also provides the use of the electric anode membrane described in the above technical solution or the electric anode membrane prepared by the preparation method described in the above technical solution in continuous flow treatment of metal organic complexes.
[0030] Preferably, the metal-organic complex is Ni-EDTA; and the metal-organic complex solution comprises a sodium sulfate electrolyte with a concentration of 0.05M.
[0031] The present invention provides an electric anode film, comprising a substrate film and a composite electrocatalyst stacked in sequence, wherein the composite electrocatalyst comprises a modified titanium dioxide nanotube array and a lead dioxide-doped iron oxide catalyst layer; the modified titanium dioxide nanotube array comprises native NTAs, Ti / TiO 2 NTAs, r-Ti / TiO 2 NTAs.
[0032] The invention grows highly ordered titanium dioxide nano-array tubes on a porous titanium substrate, thereby increasing the specific surface area and greatly improving the electrode life. In addition, the regular nano-array tube structure is used to effectively improve the charge transfer at the interface and the directional migration performance of the charge inside the titanium dioxide. Ti is doped in the titanium dioxide nano-array tubes. 3+ , overcoming the defect of poor conductivity of traditional titanium dioxide nanotube arrays; by loading lead dioxide on titanium dioxide nanotube arrays to effectively improve the oxygen evolution reaction (OER) potential, efficiently produce physically adsorbed ·OH, and completely mineralize the pollutants; at the same time, introducing iron oxide as an active dopant can effectively improve the Pb 2+The present invention utilizes the porous membrane structure of the porous titanium substrate to realize the continuous flow operation of the electro-anode membrane in the flow-through reactor, thereby increasing the contact oxidation efficiency between the pollutants and the anode surface and the active substances, and overcoming the problem of limited mass transfer of pollutants.
[0033] The electric anode film provided by the present invention overcomes the current TiO 2 The material has poor conductivity and is not easy to recycle. At the same time, it is loaded with PbO 2 The catalytic activity is greatly improved, and the doping of iron oxide further increases the electron transfer active sites of the material. The process of the present invention is simple and the reaction conditions are mild. By improving the convective mass transfer effect and generating a large amount of ·OH with strong oxidizing properties, the metal organic complex can be effectively degraded, which is expected to expand the TiO 2 Application of materials in the field of electroplating wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The Ti / TiO obtained in Example 1 2 NTAs and Ti / TiO 2 NTAs / PbO 2 - XRD pattern of Fe;
[0035] Figure 2 The Ti / TiO obtained in Comparative Example 1 2 SEM images of NTAs;
[0036] Figure 3 The Ti / TiO obtained in Comparative Example 1 2 SEM images of the cross section of NTAs;
[0037] Figure 4 The Ti / TiO obtained in Example 1 2 NTAs / PbO 2 - SEM image of Fe;
[0038] Figure 5 The Ti / TiO obtained in Example 1 2 NTAs / PbO 2 -XPS pattern of Fe;
[0039] Figure 6 The Ti / TiO obtained in Example 1 2 NTAs and Ti / TiO 2 NTAs / PbO 2 - Cyclic voltammogram of Fe;
[0040] Figure 7The Ti / TiO obtained in Example 1 2 NTAs and Ti / TiO 2 NTAs / PbO 2 -Fe degradation test results of Ni-EDTA pollutant solution;
[0041] Figure 8 The Ti / TiO obtained in Example 1 2 NTAs / PbO 2 -Fe degradation test results of Ni-EDTA pollutant solution in different modes;
[0042] Fig. 9 The Ti / TiO obtained in Example 1 2 NTAs / PbO 2 -Fe degradation test results of Ni-EDTA pollutant solution at different current densities. DETAILED DESCRIPTION
[0043] The present invention provides an electric anode film, comprising a substrate film and a composite electrocatalyst stacked in sequence, wherein the composite electrocatalyst comprises a modified titanium dioxide nanotube array and a lead dioxide-doped iron oxide catalyst layer; the modified titanium dioxide nanotube array comprises native NTAs, Ti / TiO 2 NTAs, r-Ti / TiO 2 NTAs.
[0044] In the present invention, the inner diameter of the titanium dioxide nanoarray tube is preferably 20-120 nm, the outer diameter is preferably 50-200 nm, and the length is preferably 2.0-4.0 μm; the inner diameter is further preferably 40-100 nm, more preferably 50-80 nm; the outer diameter is further preferably 50-150 nm, more preferably 60-130 nm; the length is further preferably 2.6-3.5 μm, more preferably 2.9-3.4 μm.
[0045] The present invention also provides a method for preparing the electric anode film described in the above technical solution, comprising the following steps:
[0046] The porous titanium substrate is placed in an acid solution for acidification pretreatment, and after standing for a period of time, a pretreated substrate is obtained;
[0047] The pretreated porous titanium substrate is sequentially subjected to first anodization, ultrasonic stripping, second anodization, and ultrasonic cleaning to obtain native NTAs;
[0048] The native NTAs were calcined to obtain anatase-type titanium dioxide nanotube array supported on a titanium substrate, denoted as Ti / TiO 2 NTAs;
[0049] The Ti / TiO 2 NTAs are placed in a reducing solution for cathode reduction to obtain Ti 3+ Doped titanium dioxide nanotube array, denoted as r-Ti / TiO 2 NTAs;
[0050] The r-Ti / TiO 2 The NTAs are placed in a deposition solution and electrochemically deposited using a direct current power supply box to obtain the electro-anodic film.
[0051] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0052] The present invention places the porous titanium substrate in a mixed acid solution, allows it to stand for acidification, takes it out, performs ultrasonic cleaning in ethanol and deionized water in sequence, and performs vacuum drying to obtain the porous titanium substrate after acidification pretreatment.
[0053] In the present invention, the porous titanium substrate is preferably porous foamed titanium. In the present invention, the pore size of the porous titanium substrate is preferably 20 μm.
[0054] In the present invention, the acid pretreatment solution preferably comprises hydrofluoric acid, nitric acid and water; the volume ratio of hydrofluoric acid, nitric acid and water in the acid pretreatment solution is preferably 1:(2-5):(5-30); the temperature for the acid pretreatment is preferably 20-40°C, and the pretreatment time is preferably 10-60s. In the present invention, the oxide on the electrode surface can be removed by acid pretreatment.
[0055] In the present invention, the power of the ultrasonic treatment is preferably 180W, the ethanol ultrasonic cleaning time is preferably 10 minutes, and the deionized water ultrasonic cleaning time is preferably 15 minutes; the vacuum drying temperature is preferably 60 to 100°C, and the vacuum drying time is preferably 6 to 24 hours. In the present invention, the acidic solution remaining on the electrode after acidification can be removed by ultrasonic treatment, providing a template basis for subsequent anodization.
[0056] The present invention sequentially performs first anodization, ultrasonic stripping, second anodization, ultrasonic cleaning and vacuum drying on the acidified porous titanium substrate to obtain native NTAs.
[0057] In the present invention, the electrolyte solution used in the first anodization preferably includes ammonium fluoride, ethylene glycol and water; the mass ratio of ammonium fluoride, ethylene glycol and water in the first anodization electrolyte solution is preferably 1:(3-6):(200-300); the cathode of the first anodization preferably includes a graphite plate, a titanium sheet or a platinum sheet; the distance between the anode and cathode is preferably 1-4 cm; the anodization temperature is preferably 20-40°C, the oxidation time is preferably 0.5-10h, and the oxidation voltage is preferably 20-120V.
[0058] In the present invention, the ultrasonic stripping is preferably carried out in water. In the present invention, the power of the ultrasonic treatment is preferably 180w, and the time is preferably 5 to 30min. In the present invention, the carbon dioxide nanoarray tubes grown on the surface by the first anodization can be stripped by ultrasonic treatment, and the carbon dioxide nanoarray tube growth sites are left, providing a template basis for the subsequent second anodization.
[0059] In the present invention, the electrolyte solution used in the second anodization preferably includes ammonium fluoride, ethylene glycol and water; the volume ratio of ammonium fluoride, ethylene glycol and water in the second anodization electrolyte solution is preferably 1: (2-5): (300-500); the cathode of the second anodization preferably includes a graphite plate, a titanium sheet or a platinum sheet; the distance between the anode and cathode is preferably 1-4 cm; the anodization temperature is preferably 20-40°C, the oxidation time is preferably 0.5-10h, and the oxidation voltage is preferably 20-120V.
[0060] In the present invention, the ultrasonic cleaning is preferably carried out in anhydrous ethanol and deionized water in sequence. In the present invention, the power of the ultrasonic treatment is preferably 180w, and the time is preferably 5 to 30min. In the present invention, the electrolyte solution remaining on the surface and inside of the electrode can be removed by ultrasonic treatment in anhydrous ethanol and deionized water.
[0061] In the present invention, the vacuum drying temperature is preferably 60 to 100° C., and the vacuum drying time is preferably 6 to 24 hours.
[0062] The present invention calcines the original NTAs that have been anodized twice to convert the amorphous TiO 2 Converted into anatase type to obtain Ti / TiO 2 NTAs.
[0063] In the present invention, the calcination temperature is preferably 200-500°C, more preferably 300-450°C, and more preferably 300-400°C; the heating rate to the calcination temperature is preferably <10°C / min, and more preferably 5°C / min; the holding time is 0.5-8h, more preferably 1-5h, and more preferably 2-4h.
[0064] The present invention combines Ti / TiO 2 NTAs are electrochemically reduced to partially 4+ Reduction to Ti 3+ , and then vacuum dried to obtain r-Ti / TiO 2 NTAs.
[0065] In the present invention, the solution composition of the cathode reduction preferably includes sulfuric acid and water, and the volume ratio thereof is 1:10-200; the anode of the cathode reduction preferably includes a graphite plate, a titanium sheet or a platinum sheet, and the distance between the cathode and the cathode is preferably 1-4 cm; the cathode reduction temperature is preferably 20-60°C, the reduction time is preferably 5-30 min, and the reduction current density is preferably 1-20 mA / cm 2 .
[0066] In the present invention, the cleaning solution is preferably deionized water, the number of cleaning times is preferably 3 to 5 times, and the single cleaning time is preferably 15 to 30 seconds.
[0067] In the present invention, the vacuum drying temperature is preferably 60 to 100° C., and the vacuum drying time is preferably 6 to 24 hours.
[0068] The present invention combines r-Ti / TiO 2 NTAs are placed in a deposition solution, electrochemically deposited using a DC power supply box, and then vacuum dried after cleaning to obtain the electrochemical anode film (Ti / TiO 2 NTAs / PbO 2 -Fe).
[0069] In the present invention, the deposition solution preferably comprises an acid solution, a soluble lead source, a soluble iron source, and a soluble fluorine source; the molar concentration of the deposition solution is preferably 0.01 to 1 mol / L; the type of the acid solution is preferably nitric acid; the molar concentration of the acid solution is preferably 0.01 to 1 mol / L; the soluble lead source in the deposition solution is preferably Pb(NO 3 ) 2 The soluble lead source is preferably added in the form of 0.01-1 mol / L; the soluble iron source in the deposition solution is preferably Fe(NO 3 ) 3 9H 2O, and the concentration of the soluble iron source is preferably 0.01-1 mol / L; the soluble fluorine source in the deposition solution is preferably added in the form of NaF, and the concentration of the soluble fluorine source in the deposition solution is 0.01-1 mol / L; the cathode of the deposition reaction preferably includes a graphite plate, a titanium sheet or a platinum sheet, and the distance between the anode and cathode is preferably 1-4 cm; the temperature of the deposition reaction is preferably 30-60°C, the deposition time is preferably 10-60 min, and the deposition current density is preferably 10-50 mA / cm 2 .
[0070] In the present invention, the cleaning solution is preferably deionized water, the number of cleaning times is preferably 3 to 5 times, and the single cleaning time is preferably 15 to 30 seconds.
[0071] In the present invention, the vacuum drying temperature is preferably 60 to 100° C., and the vacuum drying time is preferably 6 to 24 hours.
[0072] The present invention also provides the use of the electric anode membrane described in the above technical solution or the electric anode membrane prepared by the preparation method described in the above technical solution in the field of degrading organic pollutants.
[0073] In order to further illustrate the present invention, an electric anode membrane provided by the present invention and its preparation method and application are described in detail below in combination with the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0074] Example 1
[0075] The porous titanium foam with a pore size of 20 μm was placed in a mixed acid solution at 25°C (wherein, hydrofluoric acid: nitric acid: water = 1:3:21), taken out after acidification for 30 seconds, placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, placed in deionized water for ultrasonic cleaning for 15 minutes, and placed in a vacuum drying oven at 80°C for 8 hours to obtain an acidified porous titanium substrate.
[0076] Dissolve 2.5g of ammonium fluoride in 10mL of deionized water, and dilute to 500mL with ethylene glycol solution to obtain the first anodized electrolyte solution; use the acidified porous titanium substrate as the anode and the graphite of the same area as the cathode, place the anode and cathode in the first anodized electrolyte solution, and perform anodization at a distance of 3cm between the cathode and cathode, a voltage of 60V, and a temperature of 30°C for 1h. Place the oxidized anode in deionized water and perform ultrasound at a power of 180W for 15min to obtain the first anodized porous titanium substrate;
[0077] Dissolve 1.0g of ammonium fluoride in 5mL of deionized water, and adjust the volume to 500mL with ethylene glycol solution to obtain a second anodic oxidation electrolyte solution; use the porous titanium substrate after the first anodic oxidation as the anode, and the graphite of the same area as the cathode, place the anode and cathode in the second anodic oxidation electrolyte solution, and carry out anodic oxidation under the conditions of a cathode-cathode distance of 3cm, a voltage of 60V, and a temperature of 30°C for 4h. First, place the oxidized anode in anhydrous ethanol and perform ultrasound at a power of 180W for 10min. Place the anode after ultrasound in anhydrous ethanol in deionized water and perform ultrasound at a power of 180W for 10min. After the ultrasound, vacuum dry at 80°C for 12h to obtain native NTAs;
[0078] The grown native NTAs were placed in a tube furnace and calcined at a heating rate of 5°C / min to 350°C in an air atmosphere. The temperature was kept at this temperature for 2 h to obtain a titanium substrate with anatase-type titanium dioxide nanotube arrays grown thereon, which was denoted as Ti / TiO 2 NTAs (where the inner diameter of the titanium dioxide nanotubes is 50-80 nm, the outer diameter is 60-130 nm, and the length is 2.9-3.4 μm);
[0079] 1.103 mL of 18.4 mol / L concentrated sulfuric acid was mixed with 98.897 mL of deionized water and ultrasonicated for 10 min to obtain a 0.2 mol / L sulfuric acid reduction solution.
[0080] Ti / TiO 2 NTAs were placed in a reducing solution at a current density of 3 mA / cm 2 The Ti 3+ Doped titanium dioxide nanotube array, denoted as r-Ti / TiO 2 NTAs.
[0081] 16.5605 g Pb(NO 3 ) 2 、1.616g Fe(NO 3 ) 3 9H 2 O, 0.20995g NaF was diluted to 100mL with nitric acid solution (concentration of 0.1mol / L), and ultrasonicated for 30min to obtain a deposition solution;
[0082] r-Ti / TiO 2 NTAs were placed in the deposition solution at a current density of 20 mA / cm 2 The electrochemical deposition was carried out for 30 min under the conditions of 60°C to obtain the anode film (Ti / TiO 2NTAs / PbO 2 -Fe).
[0083] Comparative Example 1
[0084] The porous titanium foam with a pore size of 20 μm was placed in a mixed acid solution at 25°C (wherein, hydrofluoric acid: nitric acid: water = 1:3:21), taken out after acidification for 30 seconds, placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, placed in deionized water for ultrasonic cleaning for 15 minutes, and placed in a vacuum drying oven at 80°C for 12 hours to obtain an acidified porous titanium substrate.
[0085] Dissolve 2.5g of ammonium fluoride in 10mL of deionized water, and dilute to 500mL with ethylene glycol solution to obtain the first anodized electrolyte solution; use the acidified porous titanium substrate as the anode and the graphite of the same area as the cathode, place the anode and cathode in the first anodized electrolyte solution, and perform anodization at a distance of 3cm between the cathode and cathode, a voltage of 60V, and a temperature of 30°C for 2h. Place the oxidized anode in deionized water and perform ultrasound at a power of 180W for 15min to obtain the first anodized porous titanium substrate;
[0086] Dissolve 1.0g of ammonium fluoride in 5mL of deionized water, and adjust the volume to 500mL with ethylene glycol solution to obtain a second anodic oxidation electrolyte solution; use the porous titanium substrate after the first anodic oxidation as the anode, and the graphite of the same area as the cathode, place the anode and cathode in the second anodic oxidation electrolyte solution, and carry out anodic oxidation under the conditions of a cathode-cathode distance of 3cm, a voltage of 60V, and a temperature of 30°C for 4h. First, place the oxidized anode in anhydrous ethanol and perform ultrasound at a power of 180W for 10min. Place the anode after ultrasound in anhydrous ethanol in deionized water and perform ultrasound at a power of 180W for 10min. After the ultrasound, vacuum dry at 80°C for 12h to obtain native NTAs;
[0087] The grown native NTAs were placed in a tube furnace and calcined at a heating rate of 5°C / min to 350°C in an air atmosphere. The temperature was kept for 3 h to obtain a titanium substrate with anatase-type titanium dioxide nanotube arrays grown after calcination, which was denoted as Ti / TiO 2 NTAs (where the inner diameter of the titanium dioxide nanotubes is 50-80 nm, the outer diameter is 60-130 nm, and the length is 2.9-3.4 μm);
[0088] 1.103 mL of 18.4 mol / L concentrated sulfuric acid was mixed with 98.897 mL of deionized water and ultrasonicated for 10 min to obtain a 0.2 mol / L sulfuric acid reduction solution.
[0089] Ti / TiO 2 NTAs were placed in a reducing solution at a current density of 3 mA / cm 2 The Ti 3+ Doped titanium dioxide nanotube array, denoted as r-Ti / TiO 2 NTAs.
[0090] 16.5605 g Pb(NO 3 ) 2 、1.616g Fe(NO 3 ) 3 9H 2 O, 0.20995g NaF was diluted to 100mL with nitric acid solution (concentration of 0.1mol / L), and ultrasonicated for 30min to obtain a deposition solution;
[0091] r-Ti / TiO 2 NTAs were placed in the deposition solution at a current density of 30 mA / cm 2 The electrochemical deposition was carried out for 60 min under the conditions of 60°C to obtain the anode film (Ti / TiO 2 NTAs / PbO 2 -Fe).
[0092] Characterization and performance testing
[0093] Test Example 1
[0094] Figure 1 The XRD diagram of the titanium dioxide nanotube array and the anode film obtained in Example 1 is shown in FIG. Figure 1 It can be seen that after calcination, the obtained nanotubes are anatase-type titanium dioxide, and the deposited lead dioxide is β-PbO 2 .
[0095] Figure 2 This is a SEM image of a titanium substrate with titanium dioxide nanotube arrays grown thereon obtained in Comparative Example 1;
[0096] Figure 3 This is a SEM image of the cross section of the titanium substrate on which the titanium dioxide nano-array tubes are grown, obtained in Comparative Example 1;
[0097] Figure 4 is a SEM image of the anode film obtained in Example 1;
[0098] from Figures 2 to 4 It can be seen that titanium dioxide is in a vertical array structure, and pyramid-shaped lead dioxide is deposited on the titanium dioxide nanoarray tubes.
[0099] Figure 5 The Fe 2p fine spectrum of the anode film XPS obtained in Example 1 is shown in Figure 5 It can be seen that the deposited Fe is mainly Fe 3+ ;
[0100] Figure 6 The titanium substrate (referred to as Ti / TiO 2 NTAs) and the electro-anodic film (denoted as Ti / TiO 2 NTAs / PbO 2 -Fe) cyclic voltammetry curve, from Figure 6 It can be seen that the electrochemical active area of the material loaded with lead dioxide doped with iron oxide is larger.
[0101] Test Example 2
[0102] Prepare a pollutant solution containing Ni-EDTA at a concentration of 0.3 mM, with 0.05 M Na 2 SO 4 The solution serves as a supporting electrolyte;
[0103] The titanium substrate (referred to as Ti / TiO 2 NTAs) and the electro-anodic film (denoted as Ti / TiO 2 NTAs / PbO 2 -Fe) as the anode and the titanium mesh as the cathode; the cathode and cathode were placed in a filtration device, the peristaltic pump provided a flow rate of 30 mL / min, and the distance between the cathode and cathode was 1 cm; a DC power supply (constant current density of 10 mA / cm 2 )conduct.
[0104] During the test, Ni-EDTA solution was collected and analyzed at different times. The test results are as follows: Figure 7 As shown in Table 1;
[0105] Table 1 Degradation effect of the electro-anodic membrane obtained in Example 1 on Ni-EDTA
[0106] Material <![CDATA[Ti / TiO 2 NTAs]]> <![CDATA[Ti / TiO 2 NTAs / PbO2-Fe]]> Degradation efficiency (%) 45.79 80.36
[0107] It can be seen from Table 1 that under the same degradation conditions, the 2 Compared with NTAs electrodes, Ti / TiO 2 NTAs / PbO 2 -The degradation efficiency of Fe electrode is high.
[0108] Test Example 3
[0109] Prepare a pollutant solution containing Ni-EDTA at a concentration of 0.3 mM, with 0.05 M Na 2 SO 4 The solution serves as a supporting electrolyte;
[0110] The anode film and titanium mesh obtained in Example 1 were used as anode and cathode respectively; the distance between the cathode and cathode was 1 cm;
[0111] Pollutant degradation was performed under the conditions of a filtration device (Flow-through) and a beaker (Flow-by). The electrocatalytic oxidation experiment used a DC power supply (constant current density of 10 mA / cm 2 ) was performed; the peristaltic pump in the filtration device provided a flow rate of 30 mL / min; the rotor speed in the beaker was set to 100 rpm
[0112] During the test, Ni-EDTA solution was collected at different times and analyzed. The test results are as follows: Figure 8 As shown in Table 2;
[0113] Table 2 Degradation effect of the electro-anodic membrane obtained in Example 1 on Ni-EDTA
[0114] Degradation conditions Flow-through Flow-by Degradation efficiency (%) 80.36 67.08
[0115] It can be seen from Table 2 that under different degradation conditions, the degradation efficiency of the electro-anodic membrane in the Flow-through mode is the highest.
[0116] Test Example 4
[0117] Prepare a pollutant solution containing Ni-EDTA at a concentration of 0.3 mM, with 0.05 M Na 2 SO 4 The solution serves as a supporting electrolyte;
[0118] The electro-anodic film and titanium mesh obtained in Example 1 were used as anode and cathode respectively; the cathode and cathode were placed in a suction filtration device, the peristaltic pump provided a flow rate of 30 mL / min, and the distance between the cathode and cathode was 1 cm; the electrocatalytic oxidation experiment used a DC power supply to change the current density to 5, 10, and 15 mA / cm 2 .
[0119] During the test, Ni-EDTA solution was collected and analyzed at different times. The test results are as follows: Fig. 9 As shown in Table 3;
[0120] Table 3 Degradation effect of the electro-anodic membrane obtained in Example 1 on Ni-EDTA
[0121]
[0122] It can be seen from Table 3 that under the same degradation conditions, the current density is 10mA / cm 2 The degradation efficiency of Ni-EDTA is the highest.
[0123] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An electric anode membrane, characterized in that The invention comprises a substrate film and a composite electrocatalyst which are stacked in sequence. The composite electrocatalyst comprises a modified titanium dioxide nano-array tube and a lead dioxide-doped iron oxide catalytic layer. The modified titanium dioxide nano-array tube comprises native NTAs, Ti / TiO2 NTAs and r-Ti / TiO2 NTAs.
2. The electric anode membrane according to claim 1, characterized in that The titanium dioxide nanotube array has an inner diameter of 20 to 120 nm, an outer diameter of 50 to 200 nm, and a length of 2.0 to 4.0 μm.
3. A method for preparing an electric anode film, characterized in that: The preparation method comprises the following steps: The porous titanium substrate is placed in an acid solution for acidification pretreatment, and after standing for a period of time, a pretreated substrate is obtained; The pretreated porous titanium substrate is sequentially subjected to first anodization, ultrasonic stripping, second anodization, and ultrasonic cleaning to obtain native NTAs; The native NTAs are calcined to obtain anatase-type titanium dioxide nanotube arrays supported on a titanium substrate, which are denoted as Ti / TiO2 NTAs; The Ti / TiO2 NTAs are placed in a reducing solution for cathode reduction to obtain Ti 3+ doped TiO2 nanotube arrays, denoted as r-Ti / TiO2 NTAs; The r-Ti / TiO2 NTAs are placed in a deposition solution and electrochemically deposited using a direct current power supply box to obtain the electro-anodic film.
4. The preparation method according to claim 3, characterized in that: The acid solution comprises hydrofluoric acid, nitric acid and water in a volume ratio of 1:(2-5):(5-30); the temperature for the acidification pretreatment is 20-40° C., and the pretreatment time is 10-60 seconds.
5. The preparation method according to claim 3, characterized in that: The first anodic oxidation solution comprises ammonium fluoride, water, and ethylene glycol in a mass ratio of 1:(3-6):(200-300); the anodic oxidation cathode comprises a graphite plate, a titanium sheet, or a platinum sheet, and the distance between the cathode and the anode is 1-4 cm; the anodic oxidation temperature is 20-40° C., the oxidation time is 0.5-10 h, and the oxidation voltage is 20-120 V; The ultrasonic peeling solution comprises deionized water or anhydrous ethanol; the ultrasonic peeling power is 80 to 200 W; the ultrasonic peeling time is 5 to 30 minutes; The solution composition of the second anodizing includes ammonium fluoride, water, and ethylene glycol, and the volume ratio thereof is 1:(2-5):(300-500); the cathode of the anodizing includes a graphite plate, a titanium sheet, or a platinum sheet, and the distance between the cathode and the anode is 1-4 cm; the anodizing temperature is 20-40° C., the oxidation time is 0.5-10 h, and the oxidation voltage is 20-120 V; The ultrasonic cleaning solution comprises deionized water or anhydrous ethanol; the ultrasonic cleaning power is 80 to 200 W; and the ultrasonic cleaning time is 5 to 30 minutes.
6. The preparation method according to claim 3, characterized in that: The calcination temperature is 200-500° C., the heating rate to the calcination temperature is less than 10° C. / min, and the heat preservation time is 0.5-8h.
7. The preparation method according to claim 3, characterized in that: The cathode reduction solution comprises sulfuric acid and water in a volume ratio of 1:10 to 200; the cathode reduction anode comprises a graphite plate, a titanium sheet or a platinum sheet, and the distance between the cathode and the cathode is 1 to 4 cm; the cathode reduction temperature is 20 to 60°C, the reduction time is 5 to 30 minutes, and the reduction current density is 1 to 20 mA / cm 2 .
8. The preparation method according to claim 3, characterized in that: The deposition solution comprises an acid solution, a soluble lead source, a soluble iron source, and a soluble fluorine source; the molar concentration of the deposition solution is 0.01 to 1 mol / L; the type of the acid solution comprises nitric acid, hydrochloric acid or sulfuric acid; the molar concentration of the acid solution is 0.01 to 1 mol / L; the soluble lead source in the deposition solution comprises lead nitrate, lead chloride or lead sulfate, and the concentration of the soluble lead source is 0.01 to 1 mol / L; the soluble iron source in the deposition solution comprises ferric nitrate, ferric chloride or ferric sulfate, and the concentration of the soluble iron source is 0.01 to 1 mol / L; the concentration of the soluble fluorine source in the deposition solution is 0.01 to 1 mol / L; the cathode of the deposition reaction comprises a graphite plate, a titanium sheet or a platinum sheet, and the distance between the anode and cathode is 1 to 4 cm; the temperature of the deposition reaction is 30 to 60° C., the deposition time is 10 to 60 min, and the deposition current density is 10 to 50 mA / cm 2 .
9. An application of the electro-anodic membrane according to claim 1 or 2 to remove metal organic complexes in electroplating wastewater in a continuous flow system.
10. The use according to claim 9, characterized in that: The metal organic complex is Ni-EDTA; the metal organic complex solution includes a sodium sulfate electrolyte with a concentration of 0.05M.
Citation Information
Patent Citations
Method for preparing nanometer lead dioxide electrode
CN102173449A
Preparation method and application of Fe-doped PTFE-PbO2 / TiO2-NTs / Ti electrode
CN103253743A
Preparation method of autodoped modified high-conductivity TiO2 nanotube array
CN103334142A
Method for degrading ethylene diamine tetraacetic acid (EDTA) in chemical copper plating wastewater and photoelectric catalytic degradation reactor
CN104030392A
Transition metal sewage treatment method and transition metal recovery method
CN115849518A
Cited By
Preparation method and application of nickel-doped lead dioxide ozone catalytic anode
CN120573809A
Preparation method of nickel-doped lead dioxide ozone catalytic anode and application thereof
CN120573809B